Wind-induced chaotic advection in shallow flow geometries. Part II: Non-circular basins - Liang, Q; Borthwick, A; Taylor, P (2006)
The effect of flow geometry on wind-induced particle advection in non-circular shallow basins is investigated by means of a particle tracking advection model combined with a finite volume solver of the shallow water equations. A companion paper describes the numerical model and its application to horizontal mixing in circular shallow basins. The present paper considers wind-induced horizontal mixing in non-circular shallow basins, including basins of Greek hippodrome and rectangular shapes and a mine tailings pond with idealized bed topography. Wind-induced circulation in the Greek hippodrome basin moves passive tracers in a similar way to that in a circular basin, with improved mixing as the storm duration increases (within the range of values considered). For a rectangular basin, wind-induced mixing is weaker and it is not possible to achieve global chaotic advection, due to the influence of the inside corners. In the mine tailings pond, a wind varying sinusoidally both in direction and intensity is applied. The resulting mixing efficiency is high due to the intricate flow patterns resulting from the complicated domain geometry. However, global chaotic mixing is again not achieved. © 2006 International Association of Hydraulic Engineering and Research.